Cycle mechanical coefficient of useful effect of motor-transmission installations of transportation and tractor vehicles - Podrigalo Mikhail; Podrigalo Nadia; Serhii Vakhniuk; Vladyslav Bish (Avtomobilʹnyj Transport (Harʹkov))
Problem. When determining the efficiency coefficient of the motor-transmission systems of cars and tractors, it is necessary to consider not only the losses due to viscous and dry friction but also the losses caused by the circulation of potential and kinetic energy within the transmission. These losses result from the use of typical internal combustion engines in motor-transmission systems. Currently, existing studies do not take into account the dynamic cyclic energy losses in the transmission, which prevents an accurate assessment of the cyclic efficiency coefficient. Purpose. The purpose is to determine the cyclic efficiency coefficient of motor-transmission systems with internal combustion engines, taking into account the cyclic dynamic efficiency coefficient of the transmission in vehicles equipped with internal combustion engines. Methodology. The approaches adopted in this work to achieve the stated goal are based on the theoretical foundations for determining the dynamic efficiency coefficient, the work balance in the motor-transmission system of a car (or tractor) over one oscillation period of the indicator torque and the angular velocities of the engine's crankshaft during one oscillation period of its torque. Results. The cyclic mechanical fficiency coefficient of motortransmission systems in wheeled machines has been determined, accounting for the losses associated with the acceleration of moving masses and the torque irregularities inherent to internal combustion engines. A relationship has been established in which the cyclic coefficients of dynamic and elastic losses are equal to zero when the torque irregularity coefficient is zero, a characteristic typical of electric motors. Originality. The results of the study provide a general understanding of the proportionality of the cyclic dynamic coefficient of mechanical losses in the transmission to the torque irregularity coefficient and the difference between the squares of the circular frequencies of torque oscillations and the natural (free) oscillations of the transmission input shaft. Practical meaning. The obtained results can be recommended for identifying frequency coincidences that lead to resonance, where the cyclic coefficients of elastic and dynamic losses increase sharply.